Pergantian Antar Waktu Calon Legislatif Terpilih Yang Meninggal Dunia Dalam Pelaksanaan Pemilihan Umum - Widiananto Nanda Prasetya; Mohammad Syaiful Aris (Faculty of Law, Universitas Airlangga, 2024)
Recall right of political parties is a process of recalling or replacing members of The House of Representatives carried out by the carrying political parties as a form of controlling the legislative members who represent their parties, which in practice often occur in disputes or legal problems. This thesis aims to find out how the Inter-Time Alternation arrangements in the laws and regulations and what authorities are possessed by the relevant parties in the Inter-Time Alternation mechanism. In this thesis the author uses a normative juridical research method which is carried out by collecting primary legal materials, namely related legislation and literature related to the discussion material in this study and the author uses a statute approach to approach the problem. From the legal research that has been carried out using the research mentioned above, the writer concludes that the regulation of recall in the legislation is regulated in Law Number 17 of 2014 concerning People’s Consultative Assembly, The House of Representatives, Regional Representatives Council and Regional Legislative Council, Law Number 7 of 2017 concerning General Elections and Law Number 2 of 2008 concerning Political Parties which explains that political parties may apply for Inter-time dismissal of The House of Representatives members and the General Elections Commission is authorized to determine Inter-time Substitute candidates.